Cardiovascular diseases in elderly survivors of diffuse large B-cell lymphoma: a Danish population-based cohort study. Issue 9 (29th July 2022) - Juul, Maja Bech; Jelicic, Jelena; Anru, Pavithra Laxsen; Engberg, Henriette; Hammershøj Jensen, Pernille; Kristensen, Helene Bjørg; Baech, Joachim; Clausen, Michael Roost; Gang, Anne Ortved; Munksgaard, Lars; El-Galaly, Tarec Christoffer; Frederiksen, Henrik; et al.
Abstract: Diffuse large B-cell lymphoma is an aggressive disease occurring primarily in elderly patients. Despite high curative rates with doxorubicin-containing treatment, some elderly patients receive less intensive treatments, mainly due to advanced age, comorbidities, and concerns of cardiotoxicity from doxorubicin-containing regimens. We analyzed 1009 patients aged 75 years or older and 10, 090 age- and sex-matched comparisons. We aimed to evaluate long-term cardiovascular side effects in elderly patients treated with doxorubicin. Approximately, 64% of patients received doxorubicin-containing treatment. These patients had a persistently increased risk of new-onset heart failure with a hazard ratio of 1.5 and 1.7 when conditioning on survival without heart failure to 6 and 24 months, respectively. Moreover, we observed an increased risk of venous thromboembolism during the first six months following the lymphoma diagnosis. On the contrary, no difference in risk of developing ischemic heart disease or stroke following doxorubicin-containing treatment was observed.